2015
DOI: 10.1016/j.jval.2015.09.390
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis; A Zoonotic, Morbid and Fatal Disease: A Record Viewing Study

Abstract: A843body mass index (BMI) ≥ 30. 62.2% of respondents reported taking steps to lose weight. These respondents were more likely to be female, of higher socioeconomic status, and more knowledgeable about their health (all p< .05). Among respondents who were trying to lose weight, only 27.5% had consulted a specialist. The primary reason for weight loss was to improve health (60.8%). Despite these intentions, success was limited. Only 34.3% reported having lost weight in the past 6 months (43.3% reported gaining w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…20 However, it is reported that COVID-19 was closely linked to a wet market in China, and other viral diseases, such as SARS, MERS, Leptospirosis, Crimean-Congo hemorrhagic fever, Dengue, and Ebola emerged from zoonotic origins. 2,3,[27][28][29][30][31] Furthermore, about 28.8% of respondents reported incorrectly that antibiotics are the first-line treatment. At present, COVID-19 treatments include repurposing the available therapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, it is reported that COVID-19 was closely linked to a wet market in China, and other viral diseases, such as SARS, MERS, Leptospirosis, Crimean-Congo hemorrhagic fever, Dengue, and Ebola emerged from zoonotic origins. 2,3,[27][28][29][30][31] Furthermore, about 28.8% of respondents reported incorrectly that antibiotics are the first-line treatment. At present, COVID-19 treatments include repurposing the available therapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Co-linearity diagnostics was performed on variables selected for regression analysis. We considered variables with P < 0.250 in the univariate analysis as candidates for inclusion in the multivariate analysis and this is advantageous to identify more variables to be included in the multivariate analysis compared to traditional value of (P = 0.05) which may ignore important clinical parameters (30,31). Odds ratios (OR) and 95% confidence intervals (CI) were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…This trend showed an increase in 2014 with 62% confirmed cases. Up to August 2016, the virus caused 20 deaths in Pakistan [4]. In the coming near future, an exaggerated trend is expected to observe as the healthcare workers are busy in treating patients suffering from the COVID-19 and other infectious diseases [2].…”
Section: Crimean-congomentioning
confidence: 99%